INOVASI PEMBUATAN COOKIES DENGAN PENAMBAHAN KOL - ANDI HUDIAH; GAWARTI GAWARTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This research is an experimental research aimed at finding out: 1) The process of making cookies with the addition of cabbage, 2) The panelists' acceptance of making cookies with the addition of cabbage. This research was carried out at the Family Welfare Education Laboratory, Faculty of Engineering, Makassar State University. The data collection methods used are documentation, score sheets and questionnaires. The data analysis techniques used are descriptive analysis, mean, anova difference test, and duncan test. The organoleptic test results consisted of 20 panelists with the research results showing that: 1) The process of making cookies with the addition of cabbage starts from preparing tools and ingredients, weighing the ingredients, mixing the ingredients, then mixing them until evenly distributed then molding and baking. 2) Panelists' acceptance of organoleptic tests on cookie products with the addition of cabbage. The best formula produced is the F2 product. Based on the results of the respondent's assessment, 95% accepted, 0% were neutral and 5% did not accept. ABSTRAKPenelitian ini merupakan penelitian eksperimen bertujuan untuk mengetahui: 1) Proses pembuatan cookies dengan penambahan kol, 2) Penerimaan panelis terhadap pembuatan cookies dengan penambahan kol. Penelitian ini dilaksanakan di Labroratorium Pendidikan Kesejahteraan Keluarga Fakultas Teknik Universitas Negeri Makassar. Metode pengumpulan data yang digunakan adalah dokumentasi, score sheet, dan angket. Teknik analisis data yang digunakan adalah analisis deskriptif, mean, uji beda anova, dan uji duncan. Hasil uji organoleptik terdiri dari 20 orang panelis dengan hasil penelitian menunjukkan bahwa: 1) Proses pembuatan cookies dengan penambahan kol dimulai dari persiapan alat dan bahan, penimbangan bahan, pencampuran bahan, lalu dimixer hingga merata lalu dicetak dan dioven. 2) Penerimaan panelis terhadap uji organoleptik pada produk cookies dengan penambahan kol formula terbaik yang dihasilkan adalah produk F2. Berdasarkan hasil penilaian responden 95% menerima, 0% netral dan 5% tidak terima.